BIOACTIVE CONTENTS AND SOME HORTICULTURAL CHARACTERISTICS OF LOCAL APPLE GENOTYPES FROM TURKEY - M. Gundogdu; I. Canan; V. Okatan (Journal of Animal and Plant Sciences, 2018)
Some horticultural characteristics and bioactive contents of some local apple genotypes grown in Bolu province located in western black sea region were investigated. Along with the horticultural characteristics (fruit weight, width etc.), the phenolic spectrum and organic acids as bioactive content were determined. Among major phenolic compounds, catechin, -1 chlorgenic acid, gallic acid, phloridzin and rutine content varied between 10.84- 5.16 mg 100 ml ; 25.16-7.17 mg 100 -1 -1 -1 -1 ml ; 7.35- 1.42 mg 100 ml ; 6.12-1.18 mg 100 ml and 5.16-1.01 mg 100 ml , respectively. The dominant organic acids were malic acid and fumaric acid among the organic acids. When the apple genotypes were evaluated overall in terms of horticultural properties and bioctive contents; it is suggested that 14BL02, 14BL09, 14BL06 and 14BL01 genotypes displayed superior properties and they may create a significant genetic resource to be use them in breeding activities in apple in future. Institute, annual apple production in our country was
Keywords: Apple; organic acids; phenolics; pomology.